PENGGUNAAN MEDIA CANVA SEBAGAI MEDIA PEMBELAJARAN DI SEKOLAH DASAR - Agustiyani, Denis; Tianna, Vinda; Az-Zahra, Vania Sacharissa Zada; Danuri, Danuri (MIDA : Jurnal Pendidikan Dasar Islam, 2024)
The use of learning media is important and useful for improving the quality of education with the development of science and technology. One of them is Canva media. This research aims the determine the use of Canva media as a learning medium in elementary schools. This research is a literature review type. This research uses the Priferred Reporting Items For Systematic Reviews and Meta-analyses method called PRISMA. Systematic Review is a method that uses reviews, classification studies, structured evaluations, and categorization of previously produced evidence based data. So that the results of using Canva media can be used as a reference/solution in using the right application media in an innovative learning process, especially in elementary schools, because the Canva application is a unique & interesting platfrom as well as being very innovative, so it can be used as a learning media effective and efficient. Apart from that, Canva media can be a reference for educators in determining learning media so that students play a more active role in the process. However, the use of Canva media as a learning medium in elementary schools still has shortcomings, namely that Canva media has not been implemented for children with special needs in inclusive schools. So, researchers suggest that further research is needed in implementing the use of Canva media as a learning medium for children with special needs in inclusive schools.